FIGHT AGAINST DRUG ADDICTION: AN URGENT ISSUE OF MODERN SOCIETY (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes the negative impact of drug addiction on social development, public health, and youth education. It also discusses the prevention of drug addiction, strengthening preventive measures, improving medical and psychological rehabilitation systems, and enhancing cooperation between the state and society. The study is based on the analysis of legal documents, scientific literature, and recommendations of international organizations. The findings demonstrate that a comprehensive approach is necessary in combating drug addiction. The article also highlights the importance of educational programs, healthy lifestyle promotion, psychological support, and international cooperation in reducing the spread of drug abuse among young people.
Keywords: drug addiction, prevention, psychotropic substances, rehabilitation, healthy lifestyle, youth, law enforcement agencies.